2016
DOI: 10.1016/j.msea.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and tensile behavior of Fe-36%Ni alloy after cryorolling and subsequent annealing

Abstract: In this paper, the microstructure and mechanical properties of Fe-36%Ni alloy after 90% reduction of cryorolling (CR) and subsequent annealing were investigated. The X-Ray diffraction (XRD) results indicated the existence of ,   phase transformation, and the measurement result of the ,  volume fraction was 15%. Lath ,  with average thickness of 29.3 nm was then observed by transmission electron microscope (TEM). After 90% reduction of CR, the ultimate strength (UTS) of the tested alloy was enhanced to 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For the tensile test result as shown in Figure 1(d), the SZ exhibited excellent ultimate tensile strength and uniform elongation of 608 MPa and 49%, respectively, which was significantly optimised compared with that of the fusion welded, traditional FSW and severe plastic deformed Invar 36 alloy, and it seems has a good strength-ductility balance as similar as equal channel angular processed ones.
Figure 1 (a) Surface appearance and (b) cross-sectional overview of the welded joint, (c) hardness profile measured across the weld mid-thickness, (d) relationship between uniform elongation and strength of Invar 36 alloy prepared by several processing methods [1-9, 15-18]. ‘AS’ and ‘RS’ in (b) mean advancing side and retreating side of the weld, respectively.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the tensile test result as shown in Figure 1(d), the SZ exhibited excellent ultimate tensile strength and uniform elongation of 608 MPa and 49%, respectively, which was significantly optimised compared with that of the fusion welded, traditional FSW and severe plastic deformed Invar 36 alloy, and it seems has a good strength-ductility balance as similar as equal channel angular processed ones.
Figure 1 (a) Surface appearance and (b) cross-sectional overview of the welded joint, (c) hardness profile measured across the weld mid-thickness, (d) relationship between uniform elongation and strength of Invar 36 alloy prepared by several processing methods [1-9, 15-18]. ‘AS’ and ‘RS’ in (b) mean advancing side and retreating side of the weld, respectively.
…”
Section: Resultsmentioning
confidence: 99%
“…(a) Surface appearance and (b) cross-sectional overview of the welded joint, (c) hardness profile measured across the weld mid-thickness, (d) relationship between uniform elongation and strength of Invar 36 alloy prepared by several processing methods [1-9, 15-18]. ‘AS’ and ‘RS’ in (b) mean advancing side and retreating side of the weld, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The scan speed of the XRD was 2° min −1 , and the scanned angle was between 40° and 100°. The volume fraction of α ′-M was evaluated by using the equations in [7,8]. Mechanical property tests were carried out on a WDW300 materials testing machine at RT with a constant crosshead speed of 1 mm/min.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, we found that CR can significantly enhance the strength of the Fe–36%Ni alloy compared to RT rolling. In addition, both deformation twin (DT) and deformation-induced ( α ′-M) were detected during CR [7]. In this paper, the Fe–36%Ni alloy was cryorolled with thickness reduction from 20% to 90% and both the microstructural evolution and deformation mechanism were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Invar 36 alloy, which is an iron-nickel alloy with a composition in weight of 64% Fe and 36% Ni, is well known for its extremely low coefficient of thermal expansion (CTE) below Curie temperatures [1][2][3][4][5][6]. Benefiting from its extremely low expansion over a wide range of service temperatures, it has been extensively used as high precision material in engineering applications requiring high dimensional stability, such as precision instruments, space equipment, metrology devices, composite molds, and optical parts, etc.…”
Section: Introductionmentioning
confidence: 99%